Pengaruh Kompetensi, Etika Profesional dan Proses Pengendalian Manajemen terhadap Akuntabilitas Kinerja dan Fraud Akademik Akuntan Pendidik di Perguruan Tinggi Swasta Wilayah DKI Jakarta - Sigit Pamungkas; Suratno; Widarto Rachbini (Faculty of Economics and Business, University of Pancasakti Tegal, 2021)
This research was intended to examined about the influence of competencies, professional ethics and management control process on performance accountability and academic fraud of teaching accountant. The study was conducted by survey method. The data used in this research were primary data collected by questioners. Based on the results of data analysis and discussion, it was obtained the following research findings: 1) the influence of the competencies, professional ethics and management control process on performance accountability are positive and not significant; 2) the influence of the competencies, professional ethics, management control process and performance accountability on academic fraud of teaching accountant are negative and significant